2017
DOI: 10.3389/fnhum.2017.00101
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Sentence Production Processes Following Language Treatment in Aphasia: Evidence from Eyetracking

Abstract: Introduction: Sentence production impairments in aphasia often improve with treatment. However, little is known about how cognitive processes supporting sentence production, such as sentence planning, are impacted by treatment.Methods: The present study used eyetracking to examine changes in sentence production resulting from a 12-week language treatment program focused on passive sentences (Treatment of Underlying Forms (TUF); Thompson and Shapiro, 2005). In two pre-treatment and two post-treatment sessions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
12
0
1
Order By: Relevance
“…Similar priming effects have also been shown for syntactic structures: PWA were increasingly likely to produce specific syntactic structures after hearing them during a picture description task (Saffran & Martin, 1997;Cho-Reyes et al, 2016;Rossi, 2015;Hartsuiker & Kolk, 1998). In addition, sentence-level intervention based on priming mechanisms have shown to improve picture description sentences in PWA (Mack et al, 2017;Lee & Man, 2017;Weinrich et al, 2001). Priming is automatic and is hypothesized to lead to greater availability of a lexical item or syntactic structure, which then results in a lower demand on processing resources for word or sentence production.…”
mentioning
confidence: 53%
“…Similar priming effects have also been shown for syntactic structures: PWA were increasingly likely to produce specific syntactic structures after hearing them during a picture description task (Saffran & Martin, 1997;Cho-Reyes et al, 2016;Rossi, 2015;Hartsuiker & Kolk, 1998). In addition, sentence-level intervention based on priming mechanisms have shown to improve picture description sentences in PWA (Mack et al, 2017;Lee & Man, 2017;Weinrich et al, 2001). Priming is automatic and is hypothesized to lead to greater availability of a lexical item or syntactic structure, which then results in a lower demand on processing resources for word or sentence production.…”
mentioning
confidence: 53%
“…Similarly, research has repeatedly shown that the context of a sentence or a gesture restricts the number of possible expected meanings of a word (Griffin & Bock, 1998 ; Kutas & Federmeier, 2011 ; Piai et al., 2014 ; Skipper, 2014 ). This effect has also been shown in text and discourse (for a review, see van Berkum, 2009 ), supporting the idea that the language system integrates word, sentence, discourse, and common ground information to allow listeners to predict and interpret language (e.g., Barr & Keysar, 2002 ; Kutas & Federmeier, 2011 ; MacDonald et al., 1994 ). Information that is part of discourse also allows for the use of shorter references (e.g., Barr & Keysar, 2002 ; MacDonald et al., 1994 ), and the recent discourse history helps interlocutors resolve semantic-pragmatic ambiguities.…”
Section: A Review Of the Literature On Situated Language Usementioning
confidence: 64%
“…This effect has also been shown in text and discourse (for a review, see van Berkum, 2009 ), supporting the idea that the language system integrates word, sentence, discourse, and common ground information to allow listeners to predict and interpret language (e.g., Barr & Keysar, 2002 ; Kutas & Federmeier, 2011 ; MacDonald et al., 1994 ). Information that is part of discourse also allows for the use of shorter references (e.g., Barr & Keysar, 2002 ; MacDonald et al., 1994 ), and the recent discourse history helps interlocutors resolve semantic-pragmatic ambiguities. For example, the interpretation of anomalous sentences such as ‘the girl comforted the clock’ may depend on fitting within a particular context (Nieuwland & Berkum, 2006 ).…”
Section: A Review Of the Literature On Situated Language Usementioning
confidence: 64%
See 1 more Smart Citation
“…Next, we used two eyetracking tasks-to evaluate pre-to posttreatment changes in online production and comprehension of passive and active sentences. A syntactic priming task (after Cho & Thompson, 2010) was used to test production: Each trial required participants to read/ repeat an active or passive sentence and 1,500 ms later to produce a sentence describing an action scene using a different verb (Mack, Nerantzini, & Thompson, 2017). For comprehension, the aforementioned auditory sentencepicture matching task was used .…”
Section: Effect Of Treatment On Online Sentence Processingmentioning
confidence: 99%